The "Deified" Heart: Huichol Indian Soul-Concepts and Shamanic Art - MacLean, Hope (Anthropologica, 2022)
This article asks what is the relationship between shamanic vision and the production of shamanic art? Based on interviews with Huichol Indian yarn painters in Mexico, the author shows that the artist's concept of the soul is important to understanding shamanic art. For the Huichol, the heart is the centre of shamanic inspiration and the vehicle for communication with the gods. This study builds on recent research into Mesoamerican concepts of the soul, and its relationship to the human body. It questions assumptions about contemporary "ethnic and tourist" arts which arise out of the shamanic complex, and suggests that indigenous artists may be working from their own assumptions about process as well as product.